Examining the environmental impacts of materials and buildings - Brownell, Blaine Erickson, 1970- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
This book provides emerging research exploring the theoretical and practical aspects of ecological performance within modern building design and materials-based construction. Featuring coverage on a broad range of topics such as life cycle assessment, material flows analysis, and sustainability, this book is ideally designed for architects, civil engineers, construction professionals, environmentalists, ecologists, business practitioners, scientists, policymakers, designers, researchers, and academicians seeking research on current trends in environmental performance within building design.